THE INFLUENCE OF DIGITAL MARKETING AND WORD OF MOUTH ON PURCHASE DECISIONS THROUGH PURCHASE INTEREST IN MSME ROOF TILES PRODUCTS - Nawari, Nawari; Sukesi, Sukesi; Tampubolon, Liosten Rianna Roosida Ully (International Journal of Economic Integration and Regional Competitiveness, 2024)
This research is aimed at examining the direct and indirect influence of Digital Marketing and word of mouth on purchasing decisions through purchase interest tested on MSME roof tile products. The method used in this research is to use a quantitative approach. This research is included in the type of explanatory research with a sample of 100 respondents. The analysis used is structural equation modeling (SEM) with the SmartPLS application. The results of the direct influence analysis show that Digital Marketing and Word of Mouth have a positive and significant influence on purchasing interest, and Digital Marketing and Word of Mouth have a positive and significant influence on purchasing decisions. In the indirect influence test, the results show that Digital Marketing and Word of Mouth have a positive and significant influence on purchasing decisions through purchase intention.